DESIGNING AN ALUMNI TRACER STUDY INFORMATION SYSTEM USING THE RUP (RATIONAL UNIFIED PROCESS) ALGORITHM METHOD AT SMP KARYA PEMBANGUNAN MARGAHAYU - Enang Rusnandi; Syachrul Dwi Fahmi (Politeknik Mardira Indonesia, 2024)
Alumni tracer study is a search for alumni to find information through filling out questionnaires that are useful for the purpose of improving the curriculum and educational process. This research is to identify the competency profile of alumni, while at SMP KARYA PEMBANGUNAN MARGAHAYU, to provide input on improving the quality of learning according to the demands of the school sector. The absence of a centralized system for collecting data on alumni at KARYA PEMBANGUNAN SMP MARGAHAYU makes it difficult for the administration to obtain accurate information from alumni. An information system is needed as a liaison between administration and graduates by implementing this information system that is able to provide information from alumni quickly, accurately and upto-date. RUP (RATIONAL UNIFIED PROCESS) Algorithm as a system development method and My SQL as database tools. Produce an alumni track record information system that can be an administrative aid in increasing effectiveness and efficiency in the implementation of tracer study activities as well as displaying actual information in the form of alumni data reports and tracer studies quickly and accurately.